How Do Gender, Internet Activity and Learning Beliefs Predict Sixth-Grade Students’ Self-Efficacy Beliefs in and Attitudes Towards Online Inquiry? - Gonzalez-Ibanez, R (SAGE Publications Ltd, 2023)
Today’s students search, evaluate and actively use Web information in their school assignments, that is, they conduct an online inquiry. This current survey study addresses sixth-grade students’ self-efficacy beliefs in and attitudes towards online inquiry, and to what extent free-time and school-related Internet activity, gender and learning beliefs explain these. The questionnaire was administered in 10 schools to 340 sixth-graders in Finland. Exploratory and confirmatory factor analyses revealed three elements of self-efficacy beliefs: self-efficacy in Web searching, the evaluation of sources and synthesising information. Furthermore, attitudes towards online inquiry loaded into two factors: a positive and a negative attitude towards online inquiry. A structural equation model was used to analyse the effects of the explanatory variables on the factors. The results of this work suggest that gender and free-time Internet use predict most sixth-graders’ self-efficacy beliefs in and attitudes towards online inquiry. © The Author(s) 2021.